Third Trimester Lower Extremity Lymphorrhea - Kaori Morimoto; Luke O’Rourke (Case Reports in Obstetrics and Gynecology)
Introduction. Lower extremity edema is one of the most common complaints among pregnant patients. However, there is no literature mentioning weeping edema (i.e., lymphorrhea) in a pregnant woman who has no concordant underlying renal and/or cardiac pathology. There is also a lack of evidence and recommendations regarding the therapeutic benefit and safety profile of diuretic use to treat profound pregnancy-associated edema. Herein, we present the case of 32-year-old female who presented with a significant lymphorrhea during the third trimester without cardiac or renal comorbidity and was successfully treated with torsemide. Case Report. We report a case of a 32-year-old multigravida patient pregnant with her third child and has two living full-term children (G3P2003). Her pregnancy was complicated by obesity, smoking (vape), and previous history of fetal growth restriction. The patient presented for routine prenatal care at 9-week gestation. She was diagnosed with chronic hypertension at 19 weeks of pregnancy based upon systolic blood pressure>140. Lifestyle modifications were recommended, but the patient did not comply. At her 31-week office visit, the patient presented with anasarca and clear, slightly viscous fluid seeping through the atraumatic skin of her lower extremities. Preeclampsia, renal, cardiac, vascular, and infectious complications were all ruled out. The patient responded positively to loop diuretic therapy. Torsemide was found to be far more beneficial than furosemide. The patient was induced at 37 weeks secondary to chronic hypertension requiring antihypertensive therapy. Delivery was uncomplicated. The patient gave birth to a healthy male with birth weight of 2,920 g via spontaneous vaginal delivery. Discussion. Pitting edema of lower limbs frequently occurs as a result of fluid overload and chronic venous insufficiency, and pregnancy is one of the known risk factors. Additionally, the blockage of lymphatic channel with the gravida uterus likely was the main contributing factor for her lymphorrhea. In this patient, the capillary hydrostatic pressure was likely accentuated due to hypertension, obesity, and vaping. Furosemide was minimally effective to alleviate her symptoms. Torsemide provided much more effective diuresis and symptom control. However, her symptoms persisted until delivery. Conclusion. Torsemide provided significant therapeutic benefit over furosemide in this patient without adverse maternal, fetal, or neonatal outcomes. Further study is needed to assess the safe use of loop diuretics in the pregnant population who suffers from significant lower extremity edema.